Competitive intelligence practices in South African telecommunication companies - Naidoo, Aveshin (My University, 2015)
ABSTRACT Due to the pressures of recession, increases in unemployment and an uncertain economic future, business leaders are faced with huge challenges. They are met with fierce competition in the markets in which they operate as companies compete more aggressively for market share. Competitive Intelligence (CI) refers to actionable information and analysis about your competitors and your industry. Having sound, evidence-based intelligence enables business leaders to more effectively deal with competition. A CI program which involves collecting and analysing raw data and information to form actionable intelligence is fundamental to any business. Research shows however that CI is not being used with significant effect in most South African industries. This research explores the use of CI in the Telecommunications Industry of South Africa. A qualitative study using in-depth interviews was done to determine the CI process that is adopted by the major players in this industry. The degree of business leader involvement was also assessed. In order for CI to be effective it must be managed within a specific framework known specifically as the ‘intelligence cycle’. This study shows that companies within the research sample do not make use of such a framework. It also highlights the importance and pivotal role that business leaders play in having a good CI program. Companies dedicate resources to understanding what competitors are doing and make strategic decisions based on this information. Therefore the CI program that is adopted should have full support from business leaders and be managed within a framework that allows for the production of reliable intelligence
MBA 2014
Keywords: Business intelligence,Decision making, Strategic planning, Telecommunication